MEMODELKAN RASIO KETERSEDIAAN BERAS MENGGUNAKAN REGRESI DATA PANEL DINAMIS - UTAMI, NI PUTU MEILING; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 8 No 3 (2019), 2019)
The purpose of this research is to model and to determine the significant factor(s) that influence the ratio of rice availability at Province of East Java from 2007 to 2017 by applying dynamic panel data analysis. Independent variables of this research are land productivity, harvest area, and total population. The estimation method used are the first-difference GMM and system GMM. The best model to model the ratio of rice availability at Province of East Java is first-difference GMM and the independent variables which significant influence the ratio of rice availability at Province of East Java from 2007 to 2017 are lag ratio of rice availability, land productivity, harvest area, and total population.